Conversion of Cyclohexanone to Adipic Acid Catalyzed by Heteropoly Compounds - Aldes Lesbani; Fitriliana Fitriliana; Risfidian Mohadi (Universitas Gadjah Mada, 2015)
Conversion of cyclohexanone to adipic acid using hydrogen peroxide as green oxidant catalyzed by heteropoly compounds i.e. H5[a-BW12O40] H4[a-SiW12O40] and H4[a-PVMo11O40] has been carried out systematically in one pot synthesis under mild condition. The product of adipic acid was characterized using GC-MS, FT-IR, 1H-NMR and 13C-NMR spectroscopy. The results show that cyclohexanone could be converted into adipic acid by using H5[a-BW12O40] H4[a-SiW12O40] as catalysts, whereas H4[a-PVMo11O40] did not shows catalytic activity in this reaction. The effect of reaction time gave adipic acid 41% for reaction time 7 h. The yield of adipic acid was 30% with melting point 149-151 °C. The oxidation temperature at 100 °C gave the highest adipic acid 48% was obtained. The FT-IR, 1H-NMR and 13C-NMR spectra of the product are well agreed to the adipic acid standard.